2005
DOI: 10.1177/1545968305280581
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Schedule of Current Physiotherapy Treatment Used to Improve Movement Control and Functional Use of the Lower Limb after Stroke: A Precursor to a Clinical Trial

Abstract: A treatment schedule was produced, which can now be used in a subsequent phase II evaluative trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 35 publications
(46 reference statements)
0
25
0
Order By: Relevance
“…Observation of symbolic actions performed with an atypical effector could provide, for instance, a useful method of rehabilitation when the traditionally used effector is damaged or injured, by virtue of activating its motor representation. Recent studies on Action Observation Therapy have indeed confirmed the potential use of action observation as a strategy to enhance motor rehabilitation (Pomeroy et al ., ; Buccino et al ., ; Ertelt et al ., ; Mulder, ). In line with this, the present study opens the possibility of exploring new frontiers.…”
Section: Discussionmentioning
confidence: 99%
“…Observation of symbolic actions performed with an atypical effector could provide, for instance, a useful method of rehabilitation when the traditionally used effector is damaged or injured, by virtue of activating its motor representation. Recent studies on Action Observation Therapy have indeed confirmed the potential use of action observation as a strategy to enhance motor rehabilitation (Pomeroy et al ., ; Buccino et al ., ; Ertelt et al ., ; Mulder, ). In line with this, the present study opens the possibility of exploring new frontiers.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows the development of conventional physical therapy interventions as a precursor to studies evaluating novel interventions for recovery of movement after stroke. 5 Semistructured interviews and focus groups were used to capture the content of conventional physical therapy interventions. 5 study fidelity: planned versus actual treatment Trial reports should describe the extent to which the intervention, as delivered, was consistent with the protocol.…”
Section: Study Protocolmentioning
confidence: 99%
“…Figure 2⇓ shows the development of conventional physical therapy interventions as a precursor to studies evaluating novel interventions for recovery of movement after stroke. 5 Semistructured interviews and focus groups were used …”
Section: Study Protocolmentioning
confidence: 99%
“…This averaged 9.2 hours [standard deviation (SD) 6.9] for the CPT group, 7.4 hours (SD 8.6) for the CPT + MPT group, and 8.9 hours (SD 8.2) for the CPT + FST group over 6 weeks. Using a therapy protocol [13], research therapists provided the additional experimental FST and MPT, as allocated. The experimental therapies were provided for up to 1 hour per day, 4 days per week for 6 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental MPT focused on those interventions in the treatment protocol [13] that emphasised control and quality of movement. This was predominantly hands-on therapy that included sensory stimulation and preparation of body segment alignment prior to practising functional tasks, such as STS, walking, and standing with supervision and feedback.…”
Section: Methodsmentioning
confidence: 99%